1993
DOI: 10.1016/s0248-4900(05)80185-6
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural cytochemistry of the nucleus and nucleolus in growing rabbit oocytes

Abstract: Ultrastructural changes of the germinal vesicle during the growth of rabbit oocytes were studied by means of light and electron microscopy, 3H-uridine autoradiography, Ag-NOR staining and E-PTA staining. Particular interest was paid to the nucleologenesis and condensation of chromatin. In contrast to other mammalian species, chromosome condensation in rabbit oocytes occurred concomitantly with rRNA synthesis-dependent nucleolar compaction and preceded nuclear envelope breakdown and resumption of meiosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…The ultrastructural analysis showed that the agouti oocyte presented a central and regular nuclei, displaying a homogenous mass, similar to the features described for mice (Chouinard 1971), but different from hamster (Takeuchi et al 1984) and rat (Antoine et al 1987), in which the oocyte nucleoli become a compact homogenous mass at the antral follicle stage (Sutovskỳ et al 1993). It was previously reported that nucleolar compaction during oogenesis does not occur at the same stage in all species and those differences are correlated with a decrease in RNA synthesis along the follicular development (Antoine et al 1989).…”
Section: Discussionsupporting
confidence: 74%
“…The ultrastructural analysis showed that the agouti oocyte presented a central and regular nuclei, displaying a homogenous mass, similar to the features described for mice (Chouinard 1971), but different from hamster (Takeuchi et al 1984) and rat (Antoine et al 1987), in which the oocyte nucleoli become a compact homogenous mass at the antral follicle stage (Sutovskỳ et al 1993). It was previously reported that nucleolar compaction during oogenesis does not occur at the same stage in all species and those differences are correlated with a decrease in RNA synthesis along the follicular development (Antoine et al 1989).…”
Section: Discussionsupporting
confidence: 74%
“…Hall & Levison, 1990;Derenzini & Ploton, 1991;Plate et al, 1992;Rathwolfson et al, 1995), cell biology (e.g. Ploton et aI., 1987;Sutovsky et al, 1993) and developmental biology (Boloukhere, 1984;Gaginskaya et al, 1988;Standiford, 1988;Rue & Bierne, 1988;Biliriski, 1989). Several modifica-BILINSKI and BILII~ISKA tions of the technique for various biological applications have recently been suggested (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, during folliculogenesis, the molecular machinery of the oocyte is active. The nucleolus has a structure that reflects fibrogranular synthetic activity of the oocyte during growth (Sutovsky et al, 1993). During this period, the ovary synthesizes and stores large amounts of messenger ribonucleic acid (mRNA) and protein increasing their size (Motlik et al, 1989).…”
Section: Oogenesis and Follicular Developmentmentioning
confidence: 99%
“…This phase is characterized by the presence of a configuration prominent nuclear called germinal vesicle (GV) (Sutovsky et al, 1993). The peak preovulatory LH triggers the resumption of meiosis due to loss of unions "gap" between the cumulus and the oocyte, as a result of the expansion of the former.…”
Section: Nuclear Maturationmentioning
confidence: 99%
See 1 more Smart Citation